Fully porous 3D printed titanium femoral stem to reduce stress‐shielding following total hip arthroplasty. Issue 8 (4th October 2016) - Arabnejad, Sajad; Johnston, Burnett; Tanzer, Michael; Pasini, Damiano
ABSTRACT: Current hip replacement femoral implants are made of fully solid materials which all have stiffness considerably higher than that of bone. This mechanical mismatch can cause significant bone resorption secondary to stress shielding, which can lead to serious complications such as peri‐prosthetic fracture during or after revision surgery. In this work, a high strength fully porous material with tunable mechanical properties is introduced for use in hip replacement design. The implant macro geometry is based off of a short stem taper‐wedge implant compatible with minimally invasive hip replacement surgery. The implant micro‐architecture is fine‐tuned to locally mimic bone tissue properties which results in minimum bone resorption secondary to stress shielding. We present a systematic approach for the design of a 3D printed fully porous hip implant that encompasses the whole activity spectrum of implant development, from concept generation, multiscale mechanics of porous materials, material architecture tailoring, to additive manufacturing, and performance assessment via in vitro experiments in composite femurs. We show that the fully porous implant with an optimized material micro‐structure can reduce the amount of bone loss secondary to stress shielding by 75% compared to a fully solid implant. This result also agrees with those of the in vitro quasi‐physiological experimental model and the corresponding finite element model for both the optimized fully porous and fully solid implant. These studies demonstrate the merit and the potential of tuning material architecture to achieve a substantial reduction of bone resorption secondary to stress shielding. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1774–1783, 2017.